Death notice - Todd Ritter (London Avon, 2011)
erry Hollow, Pennsylvania, was always a sleepy little town...until the first body was found. Embalmed and with its lips sewn shut, the body is a horrific calling card from a killer on the lookout
Keywords: Murder -- Investigation -- Pennsylvania -- Fiction. Sheriffs -- Pennsylvania -- Fiction. Mothers -- Fiction